THE MEANING OF LIFE: A Critical Comparative Examination of Non-Christian and Christian Views on the Meaning of Life - Andrian, Hengky; Sutrisno, Sutrisno; Budiyanto, Henoch (QUAERENS: Journal of Theology and Christianity Studies, 2022)
This research seeks to find an accurate explanation of the meaning of life that is widely discussed by the 'world' with its various philosophies. Of course, there will be encounters and separations when the philosophical study of the meaning of life in general is re-examined by the study of Christian theology - which in this context the researcher uses a biblical review. The Bible is a book of mystery; revealing with 'secret' sentences like an abstract painting. Yet it contains many philosophical expressions that are no less profound, accurate, and relevant than the philosophical views of the 'world'. In this way, Christian excellence will appear to 'shine' among the various human inventions in the search for the meaning of life. Through a rigorous comparative approach, the study aims to identify common themes, points of divergence, and underlying philosophical assumptions that underpin these diverse views on life's meaning. It delves into concepts such as purpose, morality, suffering, and transcendence, seeking to uncover the underlying principles that guide individuals and communities in their pursuit of a meaningful existence. By critically evaluating these non-Christian and Christian perspectives, the research contributes to a deeper understanding of the complexities surrounding the question of life's meaning. It provides readers with a nuanced appreciation of the various intellectual and spiritual traditions that shape our understanding of human existence, ultimately inviting reflection and dialogue on this timeless and profound topic.